(3eQGbj GdadGM HEeOGO GdaJGM TQM fhQ GdEjVGM hfLGI GdCQhGMs - (3GdoqToQrfoHdGdj GdeUQj, MSf Hf YeGQ Hf Ydj, (B1069 (3g`s ((3eMeO Hf eMeO OhGLj JQceGfjs)
(3ChdgG (B:s
(3HYO GdHSedI ; hHg fSJYjf GdMeO ddg GdPj TQa NdGUI YHGOg hHYO ajbhd MSf Hf YeGQ Hf Ydj GdTQfHdGdj Ef gPG cJGH UZjQ MLeg YRjR Ydeg UMjM Mceg GMJhi Ydi eG Hg JUMjM GdYHGOGJ GdNeS HYHGQI efjQI hSejJg eQGbj GdadGM HEeOGO GdaJGM TQM fhQ GdEjVGM (B--s
(3BNQgG (B:s
(3hjbhd HYO OYGFg deG CMH jG UQjN GdeSJUQNjf jG YjGK GdeSJZjKjf jG eaQL cQH GdecQhHj jG eLjH OYhI GdeVWQjf Udj (B( (3cPG (B) (3Ydi SjOfG eMeO hBdg hGcTa cQHj hMRfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 208s
(3eYLe GdeDdajf (B1 / 575s
(3EjVGM Gdecfhf (B2 / 463s
(3gOjI GdYGQajf (B1 / 292s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs